Repairing of Flexural Cracks on Reinforced Self-Healing Concrete Beam using Bacillus Subtillis Bacteria - Prayuda, Hakas (International Journal of Integrated Engineering, 2020)
This paper will discuss the phenomenon of cracks in concrete beams due to flexural loads and methods of repair using bacteria which are often called self-healing concrete. Concrete is very good in resisting compressive forces but is weak in resisting tensile forces, so that concrete is often combined with steel reinforcement known as reinforced concrete. One interesting phenomenon is that there is damage to the concrete beam which is characterized by the occurrence of small cracks that affect the entry of oxygen into the concrete which causes corrosion of the steel reinforcement in it. To overcome this problem, the research was carried out by injecting a mixture of bacteria in the concrete, so that cracks that occur can be covered by bacteria that react with air. In this study, we will observe the flexural strength of concrete that has been repaired by using Bacillus subtillis which are injected into the concrete. Test specimens made in the form of beams measuring 150x150x600 mm as many as 8 samples will be tested for flexural strength using static loads in the center of the beam before and after bacterial injection. Flexural tests were carried out on normal concrete beams aged 7, 14, 21 and 28 days. Compressive strength is tested at 28 days with a 30 MPa strength plan. In addition, the process of closing cracks by bacteria is also carried out. From the results of the observation showed that the bacterium Bacillus subtillis could be used as an ingredient to repair concrete because the flexural strength produced after the repair is categorized as very good.